MULTI-CRITERIA EVALUATION FOR OPTIMAL ROUTE DETERMINATION BETWEEN BOSSO AND GIDAN KWANO CAMPUSES OF THE FEDERAL UNIVERSITY OF TECHNOLOGY, MINNA, NIGER STATE NIGERIA - Zitta, Nanpond; Baba, Mahmud; Olaniyi, M. Abdulmalik; Mahmood, Waziri A.; Maimuna, Bala K. (FUDMA JOURNAL OF SCIENCES, 2025)
Sustainable transport planning requires optimized road networks that minimize travel distance, reduce construction costs, and mitigate environmental degradation. Route selection, however, is inherently complex due to the heterogeneous interaction of biophysical, socio-economic, and infrastructural variables. This study employed an integrated geospatial approach, combining Remote Sensing, Geographic Information Systems (GIS), and Least Cost Path Analysis (LCPA), to delineate the optimal route between Bosso and Gidan Kwano campuses of the Federal University of Technology, Minna, Niger State, Nigeria. The Analytical Hierarchy Process (AHP) was implemented to derive criterion weights for multi-criteria decision-making, incorporating land use/land cover, slope gradient, settlement distribution, and hydrological constraints. The resultant least-cost model identified an alternative route that reduced travel distance from 15 km to approximately 13 km, translating into an estimated travel time saving of 12 minutes. Additionally, the optimized alignment circumvented built-up areas, water bodies, and rugged terrain, thereby lowering potential construction and long-term maintenance expenditures. These findings demonstrate the efficacy of coupling AHP with LCPA in optimizing linear infrastructure planning, particularly in data-scarce environments. The study contributes to sustainable transport discourse by evidencing how geospatial decision-support tools enhance route optimization, support cost-effective infrastructure development, and minimize ecological footprints. This methodological framework offers replicability for road network planning in comparable contexts, reinforcing its utility for advancing sustainable mobility and resilient infrastructure systems.